Nasal Parameters, Nostrils Shapes and Philtral Column Shape: A Morphometric Analysis in Nepalese Medical Undergraduate Students - Chalise, Usha; Dhungel, Shaligram; Chaulagain, Rajib (Journal of Nepal Health Research Council, 2019)
Background: The nose is a pyramidal shaped structure situated in the midline of midface being attached to the facial skeleton. The shape, size and spatial location of the nose-philtrum-upper lip complex are important from aesthetic point of view. Hence, to study the nasal parameters, shape of nostril and philtrum among the undergraduate students remained as the main aim of this study. Methods: This was a cross-sectional study enrolling 250 students of age 18-25 years. Nasal height, nasal width was measured and the shape of the nostrils and philtrum was recorded separately for each participant. Results: Out of 250 participants 113 were males and 137 were females. The mean nasal index of male was 75.36 while that of female was 71.72 suggesting that both genders had mesorrhine nasal type. The rectangular shaped nostrils and triangular type of philtrum was the most common types found in the study Conclusions: The study concluded that, the nasal index was mesorrhine type, the nostril was rectangular and the philtrum column was triangular in this study population. Keywords: Anthropometric; nasal index; nostrils; philtrum column shape.